First section of the Sheppards’ house, as seen from the road - Skinner, Gail M. (1978)
Photo faisant partie d'une série associée à une dissertation trimestrielle d'étudiant(e) en folklore à l'université Memorial: « Description of a house at West Bay ». -- Photo is one of a series associated with a Memorial University folklore student term paper: "Description of a house at West Bay".